Care for Money? Mortality improvements, increasing intergenerational transfers, and time devoted to the elderly - Tobias C. Vogt; Fanny Annemarei Kluge (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Background: After the reunification of Germany, mortality among older eastern Germans converged quickly with western German levels. Simultaneously, the pension benefits of eastern Germans rose tenfold. Objective: We make use of German reunification as a natural experiment to show that, first, increasing financial transfers from the elderly to their children led to increasing reverse transfers in the form of care; and, second, this rise in the number of hours spent on care led to a reduction in old-age mortality. Method: As a first step, we calculated intergenerational transfer profiles by age for eastern and western Germany to determine whether any changes in downward and in upward transfers in the form of time and money occurred since reunification. We use generalized linear regression to test whether rising pensions led to an increase in the number of hours spent on care, and whether this increase led to a reduction in old-age mortality. We use different macro level data sources to test our hypothesis, including mortality rates and time use surveys for East and West Germany and information on private intergenerational transfers from the National Transfer Accounts project for Germany. Results: We show that since German reunification, intergenerational downward transfers more than doubled in percentage terms in the east. This was predominantly caused by the sharp increase in pension benefits since the fall of the Berlin Wall. At the same time, mortality among pensioners dropped markedly, and converged 1 to western German levels. We further show that the rise in pension income was strongly correlated with the increase in social support and the decline in mortality among older eastern Germans. Discussion: Our result suggest that there was an interfamilial monetary transfer from the elderly to the young in exchange for social support. This mutual beneficial exchange may have helped to improve the survival of older East Germans after the reunification.
Keywords: 330